The only girl in the world ebook A memoir. - Julien, Maude (2017)
For readers of Room and The Glass Castle , an astonishing memoir of one woman's rise above an unimaginable childhood. Maude Julien's parents were fanatics who believed it was their sacred duty to turn her into the ultimate survivor — raising her in isolation, tyrannizing her childhood and subjecting her to endless drills designed to "eliminate weakness." Maude learned to hold an electric fence for minutes without flinching, and to sit perfectly still in a rat-infested cellar all night long (her mother sewed bells onto her clothes that would give her away if she moved). She endured a life without heat, hot water, adequate food, friendship, or any kind of affectionate treatment. But Maude's parents could not rule her inner life. Befriending the animals on the lonely estate as well as the characters in the novels she read in secret, young Maude nurtured in herself the compassion and love that her parents forbid as weak. And when, after more than a decade, an outsider managed to penetrate her family's paranoid world, Maude seized her opportunity. By turns horrifying and magical, The Only Girl in the World is a story that will grip you from the first page and leave you spellbound, a chilling exploration of psychological control that ends with a glorious escape.